Enhancement of the Fifth Generation of Wireless Communication by Using a Search Optimization Algorithm - Mohammed Jawad Al-Dujaili; ALRikabi, Haider TH.Salim; Ghanim A. Al-Rubaye; Ibtihal Razaq Niama ALRubeei (International Journal of Online and Biomedical Engineering (iJOE), 2023)
The fifth generation of cellular networks (5G) is seeing a rapid expansion, and energy efficiency (EE) is a hot topic of discussion. It has been found that both EE and maximum spectral efficiency (SE) are desired. They are conflicting objectives, meaning that maximizing one will decrease the other. To tackle this issue, strategies for spectrum and energy optimization have been proposed, as well as green communication plans that aim to minimize the tradeoff between SE and EE. Research has been conducted on EE-oriented resource allocations to reduce energy usage while ensuring high-quality results. To do this, the Crow Search Optimization Algorithm (CSA) has been used. Simulation results have demonstrated that this proposed method is effective in finding the most suitable solution.